La construcción de la política pesquera en México: Una mirada desde el campo geográfico - Santa Teresa Martínez Martínez; Fernando González Laxe (Atlantic Review of Economics, 2016)
– The evolution of the Mexican fisheries policy has occurred in diverse political, economic and social contexts, which have had different connotations, specific to the moment in which they occurred, and always with the aim of achieving an adequate administration and management of this economic activity; for this reason, the present work approaches, at first, the conceptual framework that has the development of a public policy to detonate a sector of the economy; In a second moment, the description of six key historical moments in the construction of the Mexican fishing policy, that allow to understand its present state; and in a third moment, a concentrate of the inputs-outputs of each stage is made, which favor or limit the medium and long-term development of the fishing activity. This shows the situation of a sector with a broadly functional legislative framework, but in terms of implementation has multiple weaknesses and deficiencies so that administrations can maintain the development of the fishing sector in Mexico.
Keywords: 330